EFL Undergraduate Students’ Perceptions of Online Learning Applications during the COVID-19 Outbreak - Nurmala Hendrawaty; Tri Angkarini; Ayu Bandu Retnomurti (Universitas Pendidikan Ganesha, 2021)
Covid-19 has affected the educational system worldwide, and it makes the teaching and learning process done through online learning. This study aims to investigate EFL undergraduate students’ perceptions of utilising online learning applications during the Covid-19. There were 200 participants chosen with simple random sampling. The research instrument was an online questionnaire using a Likert scale of four items. Then data analysis employed a qualitative descriptive method to analyse two indicators: experience and comfort. The findings showed that these indicators were in the same category (positive). It indicated that mostly EFL undergraduate students had positive experiences and felt convenient in operating 4 out of 10 popular online learning applications. They preferred using WhatsApp Group, Email, Google Classroom, and YouTube channel during online learning. The recommendation is that lecturers use the most favourable online learning applications and design online engaging courses so that all undergraduate students keep feeling positive, enjoyable, and motivated to take online learning during the Covid-19 outbreak.